Inventory Efficiency and Company Liquidity's Impact on Company Performance - Doaly, Thom Deutmar Londo (EAJ (Economic and Accounting Journal), 2022)
The purpose of this study is to determine whether there is (or is not) an effect of Inventory Efficiency (ITO) and Company Liquidity (QR) on Company Performance (ROA) in Textile and Garment sub-sector companies listed on the Indonesia Inventory Exchange from 2018 to 2020. In this study, Inventory Turnover (ITO) is used to measure inventory efficiency, Quick Ratio (QR) is used to measure company liquidity, and Return on Asset (ROA) is used to measure company performance. (ROA). The data used in this study is secondary data on Textile and Garment sector sub-companies listed on the Indonesia Stock Exchange between 2018 and 2020. A total of 84 samples were collected. The research method employed was descriptive qualitative. Descriptive qualitative research focuses on problems as current facts from a population. The study's findings indicate that Inventory Turnover has no effect and is insignificant on Return on Assets in the sub-sector. The company should continuously monitor and maintain the Inventory Turn Over value and the Quick Ratio value to ensure that the expected rate of return on assets (ROA) is achieved. For investors, the Inventory Turn Over and Quick Ratio values can be used to evaluate the company's ability to process inventory and liquidity.